Tryptophan Ameliorates Metabolic Syndrome by Inhibiting Intestinal Farnesoid X Receptor Signaling: The Role of Gut Microbiota–Bile Acid Crosstalk - Jiayi Chen; Hao Yang; Yingjie Qin; Xinbo Zhou; Qingquan Ma (Research)
Background and Aims: Metabolic syndrome (MS) is a progressive metabolic disease characterized by obesity and multiple metabolic disorders. Tryptophan (Trp) is an essential amino acid, and its metabolism is linked to numerous physiological functions and diseases. However, the mechanisms by which Trp affects MS are not fully understood. Methods and Results: In this study, experiments involving a high-fat diet (HFD) and fecal microbiota transplantation (FMT) were conducted to investigate the role of Trp in regulating metabolic disorders. In a mouse model, Trp supplementation inhibited intestinal farnesoid X receptor (FXR) signaling and promoted hepatic bile acid (BA) synthesis and excretion, accompanied by elevated levels of conjugated BAs and the ratio of non-12-OH to 12-OH BAs in hepatic and fecal BA profiles. As Trp alters the gut microbiota and the abundance of bile salt hydrolase (BSH)-enriched microbes, we collected fresh feces from Trp-supplemented mice and performed FMT and sterile fecal filtrate (SFF) inoculations in HFD-treated mice. FMT and SFF not only displayed lipid-lowering properties but also inhibited intestinal FXR signaling and increased hepatic BA synthesis. This suggests that the gut microbiota play a beneficial role in improving BA metabolism through Trp. Furthermore, fexaramine (a gut-specific FXR agonist) reversed the therapeutic effects of Trp, suggesting that Trp acts through the FXR signaling pathway. Finally, validation in a finishing pig model revealed that Trp improved lipid metabolism, enlarged the hepatic BA pool, and altered numerous glycerophospholipid molecules in the hepatic lipid profile. Conclusion: Our studies suggest that Trp inhibits intestinal FXR signaling mediated by the gut microbiota–BA crosstalk, which in turn promotes hepatic BA synthesis, thereby ameliorating MS.